Mapping Moral Frames: A Qualitative Analysis of Malaysian Media Coverage of the McDonald’s Boycott - Chong, Hoc Wei (Fakultas Ilmu Komunikasi Universitas Pancasila, 2025)
This study examines how Malaysian news media morally framed the McDonald’s boycott — sparked by McDonald’s Israel’s donations to the military — during the Israel-Palestine conflict in late 2023. Despite McDonald’s Malaysia’s clarifying its independence in the matter, consumer activism triggered notable reputational and economic losses. Drawing on Framing Theory and adopting a qualitative inductive content analysis of 48 online news articles between 13 October 2023 and 13 April 2024 from four Malaysian news outlets — Berita Harian, Sin Chew Daily, The Star, and Malaysiakini, the study identified six moral framing themes: victimizing workers, rational response to boycott triggers, effectiveness of boycott, selective boycotting, religious values, and freedom to boycott. Victimizing workers emerged as the dominant frame, highlighting the boycott’s unintended harm to local employees. Additionally, selective boycott appeared exclusively in Sin Chew Daily, critiquing inconsistent consumer practices. Moreover, mainstream media emphasized victimizing workers and rational response to boycott triggers, whereas alternative media paired victimizing workers with freedom of boycott. The study highlights how different linguistic and ideological media deploy moral framing to navigate complex ethical narratives amid geopolitical events. By revealing the moral themes embedded in media discourse, the findings add to the literature on media framing of morality in multicultural societies.